Neuroprotective Potency of Saffron Against Neuropsychiatric Diseases, Neurodegenerative Diseases, and Other Brain Disorders: From Bench to Bedside - Bian, Yaqi; Zhao, Chen; Lee, Simon Ming-Yuen (Frontiers in Pharmacology, 2020)
The increasing morbidity rates of brain disorders and conditions such as anxiety, depression, Alzheimer’s disease, and Parkinson’s disease has become a severe problem in recent years. Although researchers have spent considerable time studying these diseases and reported many positive outcomes, there still are limited drugs available for their treatment. As a common traditional Chinese medicine (TCM), saffron was employed to treat depression and some other inflammatory diseases in ancient China due to its antioxidant, anti-inflammatory, and antidepressant properties. In modern times, saffron and its constituents have been utilized, alone and in TCM formulas, to treat neuropsychiatric and neurodegenerative diseases. In this review, we mainly focus on recent clinical and preclinical trials of brain disorders in which saffron was applied and summarize the neuroprotective properties of saffron and its constituents from chemical, pharmacokinetic, and pharmacological perspectives. We discuss the properties of saffron and its constituents, as well as their applications for treating brain disorders; we hope that this review will serve as a comprehensive reference for studies aimed at developing therapeutic drugs based on saffron.